Penerapan Sistem Informasi Pengarsipan Surat Desa Pada Desa Brahu Kecamatan Siman Kabupaten Ponorogo - Arif Wicaksana, Febrian (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
In the current era of rapid technological development, the need for information technology is very high. This also applies to archive management, which has an important role as a source of information and functions as assessment material in decision making and preparing institutional development programs. This service program aims to develop an archive management system at the Brahu Village Hall Office, Siman District, Ponorogo Regency. Currently, management of letter archives is still done manually, so the process of searching, storing and managing letters and archival documents still requires a lot of time and energy. The results of this service program in developing and implementing a letter archiving information system at the Brahu Village Hall Office are increasing the efficiency and effectiveness of letter processing, as well as speeding up the process of searching for information and making decisions. Keywords: implementation, information systems, archives, letters